Pengembangan Aplikasi Sistem Informasi Pada Bengkel Motor Berbasis Website (Studi Kasus: Bengkel UD. Talok Jaya Motor) - Novita Kusumawardani; Denny Sagita Rusdianto; Faizatul Amalia (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Currently, the development of the automotive world, especially in Indonesia, is quite significant. One of them is marked by the high purchasing power of motorized vehicles. This is an opportunity for business people in the automotive sector to spread their wings. UD Talok Jaya Motor workshop, a general workshop located in Ngawi, has become one of the workshops that serve the sale of spare parts or motorbike service. In running its business, the workshop has a number of problems, namely the management of spare parts in and out of warehouses and storefronts, bookkeeping or income reports, and service queue management. A spare part management is needed that can control stock availability in order to make it easier to make spending plans, detailed income reports, service queue management to facilitate queue management and service queue information needs. To solve this problem, we need an information system that can help business process activities in the workshop. In the research conducted an information system development for workshops. The information system developed is website-based, the waterfall development model. Unit testing was conducted with 100% valid results in all test cases and integration testing, validation testing obtained 100% valid results, and compatibility testing resulted in the system running well on 3 web browsers used by stakeholders.